An array of staircase‐shaped circularly polarized DRA. Issue 6 (26th March 2021) - Mahmoud, Abdelhady; Ahmed, Mohamed I.; Varshney, Gaurav; Ibrahim, Ahmed A.
Abstract: A wide band circularly polarized (CP) aperture coupled staircase shaped wideband dielectric resonator antenna (SSCPDRA) array is implemented. The proposed array is composed of identical four SSCPDRA elements. The wideband CP and gain of the single element is enhanced by using 2 × 2 array with sequential phase feeding network. The measured results outputs emphasize that the proposed array is operated at frequency band from 8 to 12.3 GHz (43%). In addition, it has 3 dB axial ratio extended from 8.35 to 12.2 GHz (38.5%). Furthermore, the radiation pattern has broadside direction with the usability within the X‐band applications.